2020
DOI: 10.14483/22487638.16296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Composites Manufactured from Recycled Tetra Pak® Containers

Abstract: Context: Tetra Pak® is a common material used for the production of food containers. Currently, those containers are recycled by physical separation of the cellulose fibers through a hydro pulped process, but sometimes separating the individual components is not economically viable. This work evaluates an al­ternative process to obtain composites from recycled Tetra Pak®. Methodology: Tetra Pak® used containers were co­llected and cut into small pieces at the laboratory. Then, the containers were hot-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…While the preceding processes used shredded or ground aseptic cartons, Gallego et al [46] prepared post-consumer aseptic cartons in three ways: stacked in 5 layers without cutting; cutting into 10 mm × 15 mm slices; and cutting into 5 mm × 5 mm slices. Several cycles of pressure and temperature were applied in a manual hydraulic press with hot plates to obtain the composites which the authors concluded could be applied for non-structural purposes in the building industry.…”
Section: Layering Of Cartonsmentioning
confidence: 99%
“…While the preceding processes used shredded or ground aseptic cartons, Gallego et al [46] prepared post-consumer aseptic cartons in three ways: stacked in 5 layers without cutting; cutting into 10 mm × 15 mm slices; and cutting into 5 mm × 5 mm slices. Several cycles of pressure and temperature were applied in a manual hydraulic press with hot plates to obtain the composites which the authors concluded could be applied for non-structural purposes in the building industry.…”
Section: Layering Of Cartonsmentioning
confidence: 99%